2012
DOI: 10.17813/maiq.17.3.5m40368417v63828
|View full text |Cite
|
Sign up to set email alerts
|

Homogenizing "Old" and "New" Social Movements: A Comparison of Partipants in May Day and Climate Change Demonstrations

Abstract: We assess whether the distinction between old and new social movements still holds by examining the social class and value orientations of participants in old and new social movement protests. We argue that new cleavages have emerged from globalization, affecting not only electoral politics, but also contentious politics, and thereby having a homogenization effect on the structural basis of movements of the left. Moreover, we hypothesize that traditional cleavages, such as class mediate the homogenization effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…We selected all of the demonstrations against austerity that had been surveyed by the project during that time period in the three countries we study. Previous analysis of May Day and change demonstrations in this data-set confirmed that there has been a 'homogenising' effect across so-called old and new movements (Eggert & Giugni, 2012), which we see affirmed in the presence of universalistic goals of the demonstrations we analyse (see Appendix 2).…”
Section: Introduction and Overviewsupporting
confidence: 76%
“…We selected all of the demonstrations against austerity that had been surveyed by the project during that time period in the three countries we study. Previous analysis of May Day and change demonstrations in this data-set confirmed that there has been a 'homogenising' effect across so-called old and new movements (Eggert & Giugni, 2012), which we see affirmed in the presence of universalistic goals of the demonstrations we analyse (see Appendix 2).…”
Section: Introduction and Overviewsupporting
confidence: 76%
“…The described differences between the classes are also related to their views on the state's role: Compared with technocrats, socio-cultural specialists prefer a larger public sector and higher taxation (Güveli, 2006). Evidence from Sweden and Belgium indicates that socio-cultural specialists are especially active participants in the climate change mitigation movement (Eggert & Giugni, 2012).…”
Section: Social Classmentioning
confidence: 99%
“…; dellaPorta and Reiter (2012);Diani (2009);Eggert and Giugni (2012);Eggert and Giugni (2015);Fillieule and Blanchard (2010);Fisher, Stanley, Berman, and Neff (2005); Gómez-Román and Sabucedo (2014);Goss (2003);Heaney and Rojas (2007); Ketelaars, Walgrave, and Wouters (2014); Klandermans, Stekelenburg, Damen, Van Troost, and Van Leeuwen (2014); Nomiya (2009); Norris, Walgrave, and Van Aelst (2005); Olcese, Saunders, and Tzavidis (2014); Peterson, Wahlström, Wennerhag, Christancho, and Sabucedo (2012); Rootes and Saunders (2007); Saunders (2014); Saunders, Grasso, Olcese, Rainsford, and Rootes (2012); Stekelenburg (2006); Stekelenburg and Klandermans (2014); Stekelenburg, Klandermans, and Van Dijck (2009); Stekelenburg, Walgrave, Klandermans, and Verhulst (2012); Van Aelst and Walgrave (2001); Van Laer (2010); Verhulst and Walgrave (2009); Wahlström and Wennerhag (2014); Walgrave, Bennett, Van Laer, and Breunig (2011); Walgrave and Rucht (2010); Walgrave and Verhulst (2009); Walgrave and Wouters (2014); Walgrave, Wouters, Van Laer, Verhulst, and Ketelaars (2012); Wilson and Dunn (2011).…”
mentioning
confidence: 99%